Dampak Pengembangan Karir terhadap Kinerja Karyawan Pendidikan Tinggi Islam - Shinta Nento; Abdul Haris Abdullah (IAIN Manado, 2021)
Impact of career development on employee performance of Islamic higher education. This research is a quantitative study using primary data obtained from a questionnaire and measured using a Likert scale. The population in this study were 75 employees at Islamic higher education institutions. The method of selecting the research sample used simple random sampling without considering the strata of the members of the population because it was considered homogeneous. The measurement and testing data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using the SmartPLS 3.2 program. The results showed that career development had a positive and significant effect on employee performance. Recommendations for further research are to increase the number of research variables and use the mix method as a method to enrich the study.